STAGES OF DEVELOPMENT OF THE INSTITUTE OF PUBLIC CONTROL (World Bulletin of Management and Law, 2023)
The article analyzes the main trends in the formation and development of public institutions. In addition, the opinions and views of scientists who studied the development stage into different periods were analyzed. public control is a method of self-regulation of the social sphere. This method is implemented with the help of legal norms and components of the system to ensure order and stability. The nature, content and direction of public control is determined by the nature and type of this social system. Public control in primitive, archaic societies was completely different than in today's advanced industrial societies. In archaic societies it was simple, but in industrial societies it becomes more complicated. State control, which is one of the main mechanisms regulating the relations between society and the individual, plays an important role in the sustainable development of the country.
Keywords: public control; mass media; society; individual